Paroxysmal kinesigenic dyskinesia–like phenotype in multiple sclerosis. (November 2017) - Pop, Roxana; Kipfer, Stefan
In April 2015, a 20-year-old woman with multiple sclerosis (MS) presented with acute onset of repetitive abnormal postures and choreatic movements of the right arm, precipitated by voluntary movements (online video 1 and 2). Brain magnetic resonance imaging (MRI) showed a new active MS lesion involving the basal ganglia on the left side (Figure 1(a)). Intravenous steroid treatment resulted in rapid regression of this paroxysmal kinesigenic dyskinesia (PKD)-like hyperkinetic movement disorder. The patient became asymptomatic within 3 months. PKD is characterized by recurrent uni- or bilateral choreoathetosis and usually represents an autosomal dominant inherited disorder caused by PRRT2 gene mutations. As in the present case, a PKD-like phenotype may be associated with MS relapses in presumably genetic negative cases.